2019
DOI: 10.1175/mwr-d-18-0235.1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Typhoon Eyewalls According to World Wide Lightning Location Network Data

Abstract: Methods for the estimation of typhoon eyewall characteristics (the center location, the radius and the width, and radii of inner and outer boundaries) based on World Wide Lightning Location Network (WWLLN) data are presented and discussed in this work. The center locations, the eyewall radii, and inner boundary radii estimated from WWLLN data for the typhoons of the northwestern Pacific from 2011 to 2015 were compared with the typhoon centers, radii of maximum winds, and the radii of the eyes obtained from Adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Operational centers estimate TC intensity and structure parameters using the Dvorak method (Velden et al 2006), which is based on relationships between TC intensities and the structures of cloud fields on satellite images in the visible and infrared ranges. The RMW is defined as the distance between the warmer TC center and the colder eyewall rings, determined according to the infrared imagery of cloudtop temperature fields (Permyakov et al 2019). Because no routine reconnaissance aircraft missions for TCs have flown over the WNP since 1987, no routine or in situ observations for RMW have been conducted in the past three decades; thus, relevant studies on RMW estimates or errors are unavailable.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…Operational centers estimate TC intensity and structure parameters using the Dvorak method (Velden et al 2006), which is based on relationships between TC intensities and the structures of cloud fields on satellite images in the visible and infrared ranges. The RMW is defined as the distance between the warmer TC center and the colder eyewall rings, determined according to the infrared imagery of cloudtop temperature fields (Permyakov et al 2019). Because no routine reconnaissance aircraft missions for TCs have flown over the WNP since 1987, no routine or in situ observations for RMW have been conducted in the past three decades; thus, relevant studies on RMW estimates or errors are unavailable.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…Remote-sensed wind and wave products are operationally provided by multiple satellites, i.e., ASCAT [43], HY-2B [44], and CFOSAT [45]. Although the spatial resolution of these products is 12.5 km for winds and ~10 km for waves, they are valuable sources of data for oceanography during extreme sea states [46], e.g., typhoons and hurricanes. As mentioned above, the wind field simulated using atmospheric models such as ERA-5 during typhoons is significantly underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Price et al [13] found that in the majority of tropical cyclones, lightning frequency and maximum sustained winds are significantly correlated (mean correlation coefficient of 0.82); however, the maximum sustained winds and minimum pressures in hurricanes are preceded by increases in lightning activity approximately one day before the peak winds. Numerous other recent studies have also investigated the link between lightning and tropical cyclones [14][15][16][17]. In this study, we expand on these previous studies to investigate the role of tropical cyclones on the transport of water vapor into the upper troposphere.…”
Section: Introductionmentioning
confidence: 94%